1997
DOI: 10.1063/1.118747
|View full text |Cite
|
Sign up to set email alerts
|

4 W quasi-continuous-wave output power from 2 μm AlGaAsSb/InGaAsSb single-quantum-well broadened waveguide laser diodes

Abstract: AlGaAsSb/InGaAsSb single-quantum-well (SQW) laser diodes emitting at 2 μm were fabricated and tested. At 10–15 °C, the uncoated SQW lasers with 2–3 mm cavity lengths exhibit a threshold current density of 115 A/cm2, a continuous-wave output power of 1.9 W, a differential efficiency of 53%, and a quasi-continuous-wave output power of 4 W. Their performance deteriorates rapidly as output losses increase beyond 10 cm−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 8 publications
2
35
0
Order By: Relevance
“…All the measurements were performed at room temperature. The measured fast axis profiles for the two different injection currents, 2 1 1h and 4 Ith, were almost identical, exhibiting a Gaussian shape with full-width at half-maximum (FWHM) divergence angle of -670, which compares well with the calculated value of 60'. Figure 11 b) displays the calculated and measured transversal FF angular distribution for the above mentioned diode lasers, emitting at 1.84 and 2.34 pm.…”
Section: -234 Uim 3-qw Diode Laserssupporting
confidence: 70%
See 2 more Smart Citations
“…All the measurements were performed at room temperature. The measured fast axis profiles for the two different injection currents, 2 1 1h and 4 Ith, were almost identical, exhibiting a Gaussian shape with full-width at half-maximum (FWHM) divergence angle of -670, which compares well with the calculated value of 60'. Figure 11 b) displays the calculated and measured transversal FF angular distribution for the above mentioned diode lasers, emitting at 1.84 and 2.34 pm.…”
Section: -234 Uim 3-qw Diode Laserssupporting
confidence: 70%
“…Upon increasing the injection current, the profile shape changes, showing higher order side peaks, and the FW14M of the divergence angle increases somewhat from 4.80 (21,,) to 5.60 (41,0). 4 Ith the first and second order modes are clearly resolved. The angular position of the measured side peaks originating from higher order modes is in excellent agreement with the calculations.…”
Section: -234 Uim 3-qw Diode Lasersmentioning
confidence: 75%
See 1 more Smart Citation
“…The results indicated that the localized states are related to the Sb component of the GaAsSb alloy; however, this component also leads to poor crystal quality in the material, and the applications of GaAsSb alloys are limited owing to the deterioration in quality. InGaAsSb, which is lattice-matched to GaSb, has been studied in particular depth, in part because it is an important active region constituent of diode lasers emitting in the 2-3 µm range [23]. Early work on the direct band gap in GaSb-rich GaInAsSb has been summarized by Karouta et al, InGaAsSb, which is lattice-matched to GaSb, has been studied in particular depth, in part because it is an important active region constituent of diode lasers emitting in the 2-3 µm range [23].…”
Section: Epitaxy Of Gasb Materialsmentioning
confidence: 99%
“…InGaAsSb, which is lattice-matched to GaSb, has been studied in particular depth, in part because it is an important active region constituent of diode lasers emitting in the 2-3 µm range [23]. Early work on the direct band gap in GaSb-rich GaInAsSb has been summarized by Karouta et al, InGaAsSb, which is lattice-matched to GaSb, has been studied in particular depth, in part because it is an important active region constituent of diode lasers emitting in the 2-3 µm range [23]. Early work on the direct band gap in GaSb-rich GaInAsSb has been summarized by Karouta et al, who proposed a bowing parameter of 0.6 eV [24].…”
Section: Epitaxy Of Gasb Materialsmentioning
confidence: 99%